PENINGKATAN PENGELOLAAN KEUANGAN YAYASAN MELALUI PENGEMBANGAN SISTEM INFORMASI AKUNTANSI PADA YAYASAN AS-SHOFI DI DESA MONTONG ARE KECAMATAN KEDIRI LOMBOK BARAT - anggun hilendri lestari; Lukman Effendy; Nungki Kartikasari (https://jurnal.fe.unram.ac.id/index.php/abdimas/about/privacy, 2022)
Foundation is a non-governmental organization that operates outside the institutionalized political structure and is a volunteer service entity that aims to help others in reducing social problems. The financial statements of this foundation are needed as accounting information for users, both internal and external parties, such as donors, foundations, creditors, organizational members, and other parties for decision making (Anand, 2018). This community service activity will develop an accounting information system at a Foundation. Asshofi Raehan Lombok Foundation is a non-profit organization engaged in education. The method used in carrying out this activity is the design of an accounting information system in the form of a Foundation financial reporting application, training on the use of the application accompanied by ongoing assistance in the form of consultation if problems occur in the use of the application. Based on the results of community service, it can be concluded that the daily administrators and implementers at the Asshofi Raehan Lombok Foundation do not know about the existence of accounting standards that should be used to account for their financial management by making or compiling financial reports with applicable standards, namely using PSAK No. 45, Statement of Financial Accounting Standards concerning Financial Reporting of Non-Profit Entities.